Diagnosis of Poor Control Loop Performance: Development of a Model Based Compensation Algorithm for Control Valve Stiction Nonlinearity - N. Narayanasamy, Anand (IRC, 2016)
The objective of this paper is to develop a model based compensation algorithm using optimization approach of MIQP based MPC backlash compensator for control valve stiction nonlinearity. Optimization approach stiction compensation is very less focused and studied in the recent literatures. H. Zabiri et al proposed Mixed Integer Quadratic Programming (MIQP) based Model Predictive Controller (MPC) that uses optimization approach compensation for backlash nonlinearities in control loop. Stiction compensation is the main scope of study specifically model based compensation using optimization approach.